Effect of cropping systems in no-till farming on the quality of a Brazilian Oxisol - Seben Junior, Getulio de Freitas; Corá, José Eduardo [UNESP]; Lal, Rattan (Soc Brasileira De Ciencia Do Solo, 2014)
The no-till system with complex cropping sequences may improve the structural quality and carbon (C) sequestration in soils of the tropics. Thus, the objective of this study was to evaluate the effects of cropping sequences after eight years under the no-till system on the physical properties and C sequestration in an Oxisol in the municipality of Jaboticabal, Sao Paulo, Brazil. A randomized split-block design with three replications was used. The treatments were combinations of three summer cropping sequences -corn/corn (Zea mays L.) (CC), soybean/soybean (Glycine max L. Merryll) (SS), and soybean-corn (SC); and seven winter crops -corn, sunflower (Helianthus annuus L.), oilseed radish (Raphanus sativus L.), pearl millet (Pennisetum americanum (L.) Leeke), pigeon pea (Cajanus cajan (L.) Millsp), grain sorghum (Sorghum bicolor (L.) Moench), and sunn hemp (Crotalaria juncea L.). Soil samples were taken at the 0-10 cm depth after eight years of experimentation. Soil under SC and CC had higher mean weight diameter (3.63 and 3.55 mm, respectively) and geometric mean diameter (3.55 and 2.92 mm) of the aggregates compared to soil under SS (3.18 and 2.46 mm). The CC resulted in the highest soil organic C content (17.07 g kg(-1)), soil C stock (15.70 Mg ha(-1)), and rate of C sequestration (0.70 Mg ha(-1) yr(-1)) among the summer crops. Among the winter crops, soil under pigeon pea had the highest total porosity (0.50 m(3) m(-3)), and that under sunn hemp had the highest water stable aggregates (93.74 %). In addition, sunn hemp did not differ from grain sorghum and contained the highest soil organic C content (16.82 g kg(-1)) and also had the highest rate of C sequestration (0.67 Mg ha(-1) yr(-1)). The soil resistance to penetration was the lower limit of the least limiting water range, while the upper limit was air-filled porosity for soil bulk densities higher than 1.39 kg dm(-3) for all cropping sequences. Within the SC sequence, soil under corn and pigeon pea increased least limiting water range by formation of biopores because soil resistance to penetration decreased with the increase in soil bulk density.

O cultivo intensivo de sequências de culturas em sistema de semeadura direta proporciona o incremento de carbono (C) e a melhoria da qualidade estrutural do solo. Portanto, o objetivo deste estudo foi avaliar os efeitos de sequências de culturas em sistema de semeadura direta sobre o acúmulo de C e as propriedades físicas do solo em um Latossolo em Jaboticabal, SP, Brasil. O delineamento utilizado foi em faixas, com três repetições. Os tratamentos foram constituídos da combinação de três culturas de verão: milho/milho (Zea mays L.) (MM), soja/ soja (Glycine max L. Merryll) (SS) e soja/milho (SM); e sete culturas de inverno: milho, girassol (Helianthus annuus L.), nabo-forrageiro (Raphanus sativus L.), milheto (Pennisetum americanum (L.) Leeke), feijão-guandu (Cajanus cajan (L.) Mill sp.), sorgo (Sorghum bicolor (L.) Moench), e crotalária (Crotalaria juncea L.). O solo foi amostrado na profundidade de 0-0.10 m, após oito anos de experimentação. O solo sob SM e MM apresentou o maior diâmetro médio ponderado (3,63 e 3,55 mm) e diâmetro médio geométrico (3.55 e 2.92 mm) dos agregados, em comparação ao solo sob SS (3,18 e 2,46 mm). O MM proporcionou o maior teor de C (17,07 g kg-1), o maior estoque de C (15,70 Mg ha-1) e a maior taxa de sequestro de C (0.70 Mg ha-1 ano-1), entre as culturas de verão. Entre as culturas de inverno, o feijãoguandu proporcionou a maior porosidade total (0,50 m3 m-3), enquanto a crotalária propiciou o maior índice de estabilidade de agregados (93,74 %), o maior teor de C (16.82 g kg-1) e a maior taxa de sequestro de C (0,67 Mg ha-1 ano-1). A resistência do solo à penetração representou o limite inferior do intervalo hídrico ótimo, enquanto o limite superior foi representado pela porosidade de aeração para valores de densidade do solo maiores que 1,39 kg dm-3, determinados em todas as sequências de culturas. O milho e o feijão-guandu cultivados no SM proporcionaram o aumento do intervalo hídrico ótimo pela formação de bioporos, pois a resistência do solo à penetração diminuiu com o incremento da densidade do solo.
Sequências de culturas em sistema de semeadura direta sobre a qualidade física de um Latossolo
Keywords: Cerrado; Crop rotation; Winter crops; Soil aggregates; Least limiting water range; Bulk density; Cerrado; Rotação de culturas; Culturas de inverno; Agregados; Intervalo hídrico ótimo; Densidade do solo